DESAIN PEMBELAJARAN MATERI FUNGSI LINIER MENGGUNAKAN PEMODELAN MATEMATIKA - Dyah Rahmawati; Darmawijoyo Darmawijoyo; Hapizah Hapizah (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This research is aimed to create a learning trajectory of linear functions concept using mathematical modeling. The applied learning approach is the Model Eliciting Activities (MEAs). Design research was chosen as the research method consisting of three main phases; preliminary design, teaching experiments, and retrospective analysis. This research was conducted in class X in a public senior high school in Palembang. The result showed the design activity can encourage students to look at the form of modeling (charts/schemes/equation) that students make themself. Through steps on mathematical modeling takes students into the definition of the power to a linear functions, so the students had the idea in providing recommendations to solve real problems in life.